Study on Low-Frequency Repetitive Transcranial Magnetic Stimulation Improves Speech Function and Mechanism in Patients With Non-fluent Aphasia After Stroke - Bai, Guangtao; Jiang, Liang; Huan, Sai; Meng, Pingping; Wang, Yuyang; Pan, Xiaona; Yin, Shuai; Zhao, Yuyang; Wang, Qiang (Frontiers in Aging Neuroscience, 2022)
Objective To explore the therapeutic effect and mechanism of low-frequency repetitive transcranial magnetic stimulation on the speech function of patients with non-fluent aphasia after stroke. Methods According to the inclusion and exclusion criteria, 60 patients with post-stroke non-fluent aphasia were included and randomly divided into treatment group (rTMS group) and sham stimulation group (S-rTMS group). Patients in rTMS group were given low-frequency rTMS + ST training. Patients in the S-rTMS group were given sham low-frequency rTMS + ST training. Once a day, 5 days a week, for a total of 4 weeks. The Western Aphasia Battery and the short-form Token test were used to evaluate the language function of the patients in the two groups before and after treatment. Part of the enrolled patients were subjected to functional magnetic resonance imaging examination, and the morning fasting venous blood of the enrolled patients was drawn before and after treatment to determine the content of BDNF and TNF-α. Results In the comparison before and after treatment within the group, all dimensions of the WAB scale of the patients in the rTMS group increased significantly. Only two dimensions of the WAB scale of the patients in the S-rTMS group improved significantly after treatment. The results of the short-form Token test showed that patients in the rTMS group improved significantly before and after treatment. The resting state functional magnetic resonance imaging of the two groups of patients before and after treatment showed: the activation of multiple brain regions in the left hemisphere of the rTMS group increased compared with the control group. The serum BDNF content of the patients in the rTMS group was significantly higher than that of the patients in the S-rTMS group after treatment. Conclusion Low-frequency rTMS combined with conventional speech training can significantly improve the speech function of patients with non-fluent aphasia after stroke.